Spring CO2 dynamics within sea ice: abiotical versus biological control - Delille, Bruno; Borges, Alberto Vieira; Lannuzel, Delphine; Becquevort, Sylvie; Schoemann, Véronique; Lancelot, Christiane; de Jong, Jeroen; Tilbrook, Bronte; Delille, D.; Tison, Jean-Louis (2007)
info:eu-repo/semantics/published